Recommendations for Increasing Sour Dry Sub-Optimal Land Potential for Several Food Crops - Silvia Nora (Talenta Publisher, 2021)
Sub-optimal land is land that has low productivity due to parent material, physical, chemical, biological properties of the soil, rainfall, and extreme temperatures. To meet the availability of national food sources, it is necessary to utilize sub-optimal land that is widespread in mainland Indonesia. The purpose of the study was to determine recommendations for increasing sub-optimal land potential based on land suitability classes for several food crops, namely lowland rice, upland rice, cassava, sweet potato, corn, soybean, and peanut. The research was conducted in Stabat District, Langkat Regency from June to November 2020, and the Asian Agri Laboratory of North Sumatera Province. The research method used is the survey method, while to determine the suitability of the land, namely the matching method. Land potential in Stabat District can be increased by managing it in the form of recommendations for adding N fertilizer was 7,000 kg N/ha or the equivalent of 1,555 kg urea/ ha, the addition of P fertilizer was 158.8 Kg P2O5 or equivalent to 441 Kg SP36/ha, K fertilizer was 26.32 Kg K2O/ha or the equivalent of 43.86 Kg KCl. The adding organic matter or compost is 43.8 kg C-organic/ha or equivalent to 63.9 kg compost/ha.